Prognostic Factors for Pediatric Tumors - Kourti, Maria; Hatzipantelis, Emmanouel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue, recent advancements in the field of pediatric tumors are discussed, and novel prognostic markers are critically appraised. Greater understanding of the heterogeneity of pediatric cancers will ultimately lead to new therapeutic strategies with the potential to provide new prospects for precision medicine in pediatric oncology.